Thioredoxin 1 Negatively Regulates Angiotensin II-Induced Cardiac Hypertrophy through Upregulation of miR-98/let-7 - Yang, Yanfei (2010)
RATIONALE: Thioredoxin 1 (Trx1) inhibits pathological cardiac hypertrophy. MicroRNAs (miRNAs) are small non-coding RNAs that downregulate posttranscriptional expression of target molecules. OBJECTIVES: We investigated the role of miRNAs in mediating the anti-hypertrophic effect of Trx1 upon angiotensin II (Ang II)-induced cardiac hypertrophy. METHODS AND RESULTS: Microarray analyses of mature rodent microRNAs and qRT-PCR/Northern blot analyses showed that Trx1 upregulates members of the let-7 family, including miR-98, in the heart and the cardiomyocytes (CMs) therein. Adenovirus-mediated expression of miR-98 in CMs reduced cell size both at baseline and in response to Ang II. Knock-down of miR-98, and of other members of the let-7 family, augmented Ang II-induced cardiac hypertrophy and attenuated Trx1-mediated inhibition of Ang II-induced cardiac hypertrophy, suggesting that endogenous miR-98/let-7 mediates the anti-hypertrophic effect of Trx1. Cyclin D2 is one of the predicted targets of miR-98. Ang II significantly upregulated cyclin D2, which in turn plays an essential role in mediating Ang II-induced cardiac hypertrophy, whereas overexpression of Trx1 inhibited Ang II-induced upregulation of cyclin D2. miR-98 decreased both expression of cyclin D2 and the activity of a cyclin D2 3’UTR luciferase reporter, suggesting that both Trx1 and miR-98 negatively regulate cyclin D2. Overexpression of cyclin D2 attenuated the suppression of Ang II-induced cardiac hypertrophy by miR-98, suggesting that the anti-hypertrophic actions of miR-98 are mediated in part by downregulation of cyclin D2. CONCLUSIONS: These results suggest that Trx1 upregulates expression of the let-7 family, including miR-98, which in turn inhibits cardiac hypertrophy, in part through downregulation of cyclin D2.